Enhancement of endotoxin lethality and generation of anaphylactoid reactions by lipopolysaccharides in muramyl-dipeptide-treated mice. - Takada, H (1987)
Intravenous injection of muramyl dipeptide (MDP) and Salmonella lipopolysaccharides (LPS) enhanced lethal toxicity of the LPS in C57BL/6 mice. This was true for S (smooth)- and R (rough)-form LPS and free lipid A. Enhancement of toxicity was maximum when the LPS was administered 4 h after MDP, at which time the lethal doses for 50% of mice of S- and R-form LPS and free lipid A were between 1 and 10 micrograms, compared with more than 100 micrograms in normal animals. This sensitization was absent in endotoxin-resistant C3H/HeJ mice. Lethality usually commenced 15 h after LPS injection and was complete after 72 h. Higher doses of some S-form LPS (100 micrograms or more) administered 4 h after MDP led to a strong anaphylactoid reaction within 10 to 20 min of injection, with lethal outcomes in less than 1 h after LPS administration. This early anaphylactoid reaction was observed for various mouse strains, including LPS-resistant C3H/HeJ mice, but it was very weak or completely absent with R-form LPS or free lipid A even in concentrations of up to 1,000 micrograms. A strong anaphylactoid reaction comparable to that seen with S-form LPS was also obtained, after MDP treatment, with an LPS of low toxicity prepared from Bacteroides gingivalis. It is noteworthy that oral administration of MDP also contributed to the anaphylactoid reaction and enhanced the late-phase lethality of LPS. The present findings strongly suggest that the early- and late-phase reactions induced by MDP and LPS are caused by different mechanisms.